(untitled) (Plant Tissue Culture and Biotechnology, 2010)
In vitro shoot multiplication from nodal explants of Picrorhiza kurroa Royle ex. Benth. (Kour) was obtained on MS without cytokinin. Addition of NAA in the culture medium favours shoots as well as root formation. Among the various combinations of MS and B5 media, the average number of shoots per explant was (18.3) on MS supplemented with 0.6 mg/l NAA. Shoot length was maximum (5.8 cms) in MS augmented with 0.4 mg/l NAA. The elongated shoots rooted within 15 - 25 days either on MS alone or supplemented with NAA (0.4 mg/l), IAA and IBA (0.1 - 0.5 mg/l). About 81.5% of the rooted plantlets survived acclimation and transferred to the greenhouse. All the in vitro derived plants at maturity displayed normal development as that of the mother plants at their maturity. Key words: Picrorhiza kurroa, Hardening, Medicinal plant, Propagation D.O.I. 10.3329/ptcb.v19i2.5433 Plant Tissue Cult. & Biotech. 19(2): 161-167, 2009 (December)